Protocol of a test of hearing health education programs for farm and rural youth. (December 2015) - McCullagh, Marjorie; Banerjee, Tanima; Yang, James
Abstract Background Farm and rural youth have frequent exposure to hazardous noise on the farm and recreationally, and have an increased prevalence of noise-induced hearing loss. There is a lack of programs to prepare this high-risk population to use hearing conservation strategies. Methods The purpose of this project is to test innovative hearing health education programs delivered to a large target group and to determine the effectiveness and sustainability of these programs in promoting hearing health among farm and rural youth. Specifically, this project includes: a) an interactive face-to-face informational program alone, b) an interactive face-to-face informational program followed by an Internet-based booster, and c) a no-intervention control. Sites will include selected affiliates of a major farm youth safety education organization. Data will be collected at baseline, 3, and 12 months. A linear mixed model will be used to compare the effectiveness of the three interventions over time. Descriptive statistics will be used to compare program costs and sustainability ratings. Discussion Outcomes of this project will provide knowledge necessary to implement quality and cost-effective services to farm and rural youth, a high-risk and underserved population, that can be implemented and sustained after the study is completed. Trial registration Clinicaltrials.govNCT02472821 Registered 09 Jun, 2015.